2009
DOI: 10.1021/ja907357g
|View full text |Cite
|
Sign up to set email alerts
|

Formation of N-Alkylpyrroles via Intermolecular Redox Amination

Abstract: Redox isomerization reactions are of particular interest because they exhibit perfect atom economy, and they often utilize the inherent reducing power of hydrogen that is embedded in molecules to effect reduction of other functional groups. [1][2][3] In doing so, redox isomerizations are able to circumvent the requirement for exogenous reducing agents, which tend to be high energy reagents. The power of redox isomerizations is arguably increased when it is used in conjunction with C-X bond-forming reactions. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
37
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(39 citation statements)
references
References 21 publications
1
37
0
1
Order By: Relevance
“…6 Lastly, an indoline with an unprotected aniline was compatible with our redox amination, although the product 1i was formed in moderate yield. In addition, a benzo-fused indoline gave product 1g in good yield; benzoindoles are a basic skeleton found in several biologically active compounds.…”
mentioning
confidence: 60%
See 1 more Smart Citation
“…6 Lastly, an indoline with an unprotected aniline was compatible with our redox amination, although the product 1i was formed in moderate yield. In addition, a benzo-fused indoline gave product 1g in good yield; benzoindoles are a basic skeleton found in several biologically active compounds.…”
mentioning
confidence: 60%
“…Under these conditions, an 80% yield of 1-amino indole was isolated. The reaction did not proceed without catalyst or when using highly acidic Bi(OTf) 3 or TfOH catalysts (entries [4][5][6]. Weaker Brønsted acids are superior catalysts, with TFA giving just 25% yield while acetic acid provides the product in 63% yield (entries 7, 8).…”
mentioning
confidence: 99%
“…142 Tunge and co-workers took advantage of the reducing power of 3-pyrroline for the formation of N-alkylpyrroles by intermolecular redox amination (Scheme 43). 143 On treatment Yu and co-workers reinvestigated Tunge's work by DFT calculation and found that the one-step direct 1,3-hydrogen shift process proposed by Tunge is not viable due to the very high activation energy, even though it has been proposed in some redox isomerization reactions. Instead, they proposed the formation of acetic-acid-assisted azomethine ylide intermediate 122 (Scheme 44).…”
Section: C−h Bond Functionalizationmentioning
confidence: 99%
“…Furthermore, in the case of an allylsulfanyl group it was shown that propene was eliminated in this reaction [106]. in the presence of acids led to dehydrogenation of the heterocycle and hydrogenation of the formed Schiff base resulting in the 1-substituted pyrrole 154 [108]. The reaction with indoline 155 similarly led to the indoles 156 [109,110].…”
Section: -92%mentioning
confidence: 97%
“…The reaction with indoline 155 similarly led to the indoles 156 [109,110]. Tunge and colleagues [108] suggested that a 1,3-migration of hydrogen was the key step of this process. On the basis of quantum-chemical calculations Chinese scientists [110] proposed that the reaction took place by an intermolecular proton transfer mechanism with an activation energy of 25.6 kcal/mol in a solvent, whereas a 1,3-migration of the proton would have a barrier of 44.6 kcal/mol.…”
Section: -92%mentioning
confidence: 99%